2012
DOI: 10.1523/jneurosci.0767-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Movement-Related Changes in Local and Long-Range Synchronization in Parkinson's Disease Revealed by Simultaneous Magnetoencephalography and Intracranial Recordings

Abstract: Functional neurosurgery has afforded the opportunity to assess interactions between populations of neurons in the human cerebral cortex and basal ganglia in patients with Parkinson's disease (PD). Interactions occur over a wide range of frequencies, and the functional significance of those Ͼ30 Hz is particularly unclear. Do they improve movement, and, if so, in what way? We acquired simultaneously magnetoencephalography and direct recordings from the subthalamic nucleus (STN) in 17 PD patients. We examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
178
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 181 publications
(202 citation statements)
references
References 81 publications
21
178
3
Order By: Relevance
“…Recent models of motor control recognize the need for a general mechanism to regulate the effort expended during a task according to task demands and cost-benefit contingencies (Todorov and Jordan, 2002;Guigon et al, 2007). This function has been associated with the basal ganglia, where the function is considered to rely on dopaminergic input (Mazzoni et al, 2007;Niv and Rivlin-Etzion, 2007), in line with the interaction between dopaminergic therapy and task complexity in the current study. Although the LFP changes we describe by no means prove a role for the STN in the coding of effort, they serve to demonstrate that changes in oscillatory dynamics in the STN cannot simply be accounted for in terms of the selection and parameterization of motor variables, such as force; in our paradigm the movements made did not differ, but the resources needed to achieve them did.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Recent models of motor control recognize the need for a general mechanism to regulate the effort expended during a task according to task demands and cost-benefit contingencies (Todorov and Jordan, 2002;Guigon et al, 2007). This function has been associated with the basal ganglia, where the function is considered to rely on dopaminergic input (Mazzoni et al, 2007;Niv and Rivlin-Etzion, 2007), in line with the interaction between dopaminergic therapy and task complexity in the current study. Although the LFP changes we describe by no means prove a role for the STN in the coding of effort, they serve to demonstrate that changes in oscillatory dynamics in the STN cannot simply be accounted for in terms of the selection and parameterization of motor variables, such as force; in our paradigm the movements made did not differ, but the resources needed to achieve them did.…”
Section: Discussionsupporting
confidence: 70%
“…Previous work has demonstrated that gamma activity in the basal ganglia correlates with force or velocity, but has failed to dissociate these from effort (Anzak et al, 2012;Brücke et al, 2012;Tan et al, 2013a). One study explicitly contrasted simple, synchronous, and complex sequential finger movements and found no change in perimovement gamma activity in the STN (Litvak et al, 2012), although it could be argued that the demands of the complex task were less challenging than in the current paradigm.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations